Skype as a Synchronous Online Platform in EFL Class - Dewi Rosmala (TLEMC (Teaching and Learning English in Multicultural Contexts), 2020)
The COVID-19 pandemic has had an impact on various fields including education. The learning process shifted from face-to-face learning to distance learning. Skype is one of the platforms that is used in one of the universities in Indonesia as a medium for online learning during a pandemic situation. Therefore, this study investigated studentsâ€™ perceptions of the use of Skype as a platform for synchronous online learning because. To collect the data, this study conducted interviews with three participants from the English Education Department in one of the universities in Indonesia that use Skype as a medium for online learning during the pandemic situation one semester. The data were analyzed using thematic analysis from Braun and Clarke (2006). Underpinning Technology Acceptance Model (TAM) framework, this qualitative research documented positive perceptions toward the use of Skype based on two factors: perceived ease of use and perceived usefulness. The findings reported that there are two big themes in this research: Skype facilitates users to adapt easily and the Effectiveness of Skype application as an online learning tool.Â Keywords: EFL class, online platform, skype, synchronous.